Advances in production management systems : production management for the factory of the future : IFIP WG 5.7 International Conference, APMS 2019, Austin, TX, USA, September 1-5, 2019 : proceedings.: production management for the factory of the future : IFIP WG 5.7 International Conference, APMS 2019, Austin, TX, USA, September 1-5, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available